Walter Wanger, Hollywood Independent - Bernstein, Matthew (Book collections on Project MUSE., 2000)
A portrait of the trailblazing film producer whose career spanned five decades."Bernstein packs an astonishing amount of solid film history into his lucid chronicle of Wangers whirlwind corporate liaisons. ... A fully realized, A-line biopic of a fascinating life in the movies."Tom Doherty, Film Quarterly.